2011
DOI: 10.1016/j.juro.2010.08.089
|View full text |Cite
|
Sign up to set email alerts
|

New Ureteral Stent Design Does Not Improve Patient Quality of Life: A Randomized, Controlled Trial

Abstract: The Polaris stent, designed with the specific aim of improving urinary symptoms and pain associated with ureteral stents, continues to have a significant detrimental effect on patient quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 10 publications
0
30
0
1
Order By: Relevance
“…As has been found in multiple other survey studies, response to the USSQ survey was lower than anticipated, so that reaching our target enrolment was not possible within the constraints of the present study and may have underpowered the study to detect slight differences in patient outcomes. However, survey compliance was similar between cohorts and only slightly lower than similar studies using the USSQ as a survey tool [9,[16][17][18]. Furthermore, the accrual rate was also lower than anticipated, with only 25% of patients approached agreeing to participate.…”
Section: Discussionmentioning
confidence: 65%
“…As has been found in multiple other survey studies, response to the USSQ survey was lower than anticipated, so that reaching our target enrolment was not possible within the constraints of the present study and may have underpowered the study to detect slight differences in patient outcomes. However, survey compliance was similar between cohorts and only slightly lower than similar studies using the USSQ as a survey tool [9,[16][17][18]. Furthermore, the accrual rate was also lower than anticipated, with only 25% of patients approached agreeing to participate.…”
Section: Discussionmentioning
confidence: 65%
“…Some investigators have demonstrated (16,17) improving impact of alpha-blockers including alfuzosin and terazosin on stent-related discomforts, whereas Kuyumcuoglu et al (19) concluded that stent discomforts remained unchanged even after administering doxazosin, therefore, they argued that a new strategy and stent design are required to attenuate stent-related complications; however, a recently published study has demonstrated that the new stents did not improve stent-related symptoms (20). Considering the current study and the two meta-analyses that have been recently published (21,22), it seems that alpha-blockers can effectively relieve stent-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of the present study is of the low response rate, with only 74% of patients returning at least the week 1 questionnaire. However, the non‐return rate was similar in each group and multiple previous studies have also reported low response rates using similar questionnaires . The present study was therefore only adequately powered (>80%) at week 1 to detect the differences set out initially for the ‘urinary symptoms’ and ‘general health’ domains.…”
Section: Discussionmentioning
confidence: 99%